2020
DOI: 10.1111/cas.14555
|View full text |Cite
|
Sign up to set email alerts
|

A nuclear lncRNA Linc00839 as a Myc target to promote breast cancer chemoresistance via PI3K/AKT signaling pathway

Abstract: Chemoresistance has become a leading cause of mortality in breast cancer patients and is one of the major obstacles for improving the clinical outcome. Long noncoding RNAs play important roles in breast cancer tumorigenesis and chemoresistance. However, the involvement and regulation of lncRNAs in breast cancer chemoresistance are not completely understood. Here, we reported that Linc00839 was localized in the nucleus and upregulated in chemoresistant breast cancer cells and tissues, and high level of Linc0083… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…CTD decreases the expression of miRNA-160b-93 as a tumor-promoting factor to enhance the expression of its downstream target PTEN, resulting in breast cancer inhibition [ 306 ]. Matrine is also an alkaloid derived from Sophora flavescens with capability in regulating the expression of miRNAs in cancer therapy [ 307 ]. It is noteworthy that it has been reported that matrine can regulate the miRNA/PTEN axis in colorectal cancer therapy [ 231 ], which is the same strategy that is followed in breast cancer therapy.…”
Section: Microrna and Pten Relationshipmentioning
confidence: 99%
“…CTD decreases the expression of miRNA-160b-93 as a tumor-promoting factor to enhance the expression of its downstream target PTEN, resulting in breast cancer inhibition [ 306 ]. Matrine is also an alkaloid derived from Sophora flavescens with capability in regulating the expression of miRNAs in cancer therapy [ 307 ]. It is noteworthy that it has been reported that matrine can regulate the miRNA/PTEN axis in colorectal cancer therapy [ 231 ], which is the same strategy that is followed in breast cancer therapy.…”
Section: Microrna and Pten Relationshipmentioning
confidence: 99%
“…Long intergenic non-protein coding RNA 839 (LINC00839) was also studied in breast cancer [100] and osteosarcoma [101]. Its upregulation correlated with bad prognosis in both cases.…”
Section: Lncrna Associated With Nb Regressionmentioning
confidence: 99%
“…Its upregulation correlated with bad prognosis in both cases. In particular, Chen et al [100] described the mechanism by which this lncRNA acts in breast cancer cells: it is transcriptionally activated by MYC interaction with its promoter and can bind Lin28b, promoting positive regulation of both MYC and Lin28b protein. Despite this mechanism occurring in breast cancer cells, it is interesting to note that LIN28B overexpression promotes NB onset [102].…”
Section: Lncrna Associated With Nb Regressionmentioning
confidence: 99%
“…In breast cancers, it is reported that lncRNA BORG enhances chemo-resistant traits by binding to RPA1, which stimulates the NF-κB signaling pathway in triple-negative breast cancer [ 119 ]. Binding of LINC00839 with Lin28B impairs chemotherapeutic outcomes via the PI3K/AKT signaling pathway in breast cancer [ 120 ]. LncRNA GBCDRlnc1 binds to PGK1 and prevents its degradation to subsequently activate its downstream targets, such as ATG5-ATG12, that can induce autophagy and chemoresistance in gallbladder cancer [ 121 ].…”
Section: Lncrna–protein Interaction In Cancer Developmentmentioning
confidence: 99%